2019
DOI: 10.3906/sag-1808-86
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of low-dose Hepatitis B Immunoglobulin plus nucleos(t)ide analogs in preventing post-transplant HBV recurrence

Abstract: Background/aim: In this study, the efficiency of using low-dose HBIG plus antiviral treatment according to individual needs have been evaluated in post-transplant HBV patients. Material and methods: We retrospectively evaluated 179 patients who admitted between 2009-2014. Five thousand IU IV HBIG was given in anhepatic phase, and 400 IU/day IM HBIG was given in the post-transplant period. After HBsAg seroconversion 400 IU IM HBIG every two weeks as prophylaxis was continued. Results: Average follow-up period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Patients with additional HBV DNA positivity at time of LT, patients with HCC, and patients with HBV/HDV coinfection are particularly prone to HBV reinfection without prophylaxis. 64 , 66 , 67 Shorter courses of (lower dose) HBIG, 70 , 71 individualized dosing schedules, 72 , 73 HBIG limiting or sparing regimens, 74 and/or de novo NAs alone 75 , 76 have also been evaluated to reduce the likelihood of HBV reactivation. A recent study has reported HBsAg loss in 100% (n = 41) of patients after 1 year of entecavir monotherapy post‐LT for HBV‐related HCC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with additional HBV DNA positivity at time of LT, patients with HCC, and patients with HBV/HDV coinfection are particularly prone to HBV reinfection without prophylaxis. 64 , 66 , 67 Shorter courses of (lower dose) HBIG, 70 , 71 individualized dosing schedules, 72 , 73 HBIG limiting or sparing regimens, 74 and/or de novo NAs alone 75 , 76 have also been evaluated to reduce the likelihood of HBV reactivation. A recent study has reported HBsAg loss in 100% (n = 41) of patients after 1 year of entecavir monotherapy post‐LT for HBV‐related HCC.…”
Section: Resultsmentioning
confidence: 99%
“…1 Indeed, a larger study has reported 15% of patients under entecavir monotherapy being HBsAg positive at 1 year post‐LT. 76 HCC as an indication for LT remains a key risk factor for HBV reactivation 73 and is associated strongly with the reappearance of HBsAg after withdrawal of HBIG. 75 HBIGs are not indicated currently for the prevention of HCC recurrence post‐LT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies support the efficacy of combination of low‐dose IM HBIG with ETV (or TDF) given indefinitely as an effective prophylaxis against HBV recurrence after LT irrespectively of anti‐HBs levels 53‐56 . Vatansever et al recently reported that low‐dose IM HBIG combined with a NA (LAM, ADV, ETV, TDF or telbivudine) results in 4.5% and 5.8% of HBV recurrence in the first and third year after LT respectively 53 . Likewise, a Chinese registry indicated that low‐dose IM HBIG in combination with a NA (mainly ETV) was an effective prophylactic option against HBV recurrence 54 .…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 97%
“…Several protocols have been recommended and used regarding the dose and duration of HBIG administration in combination with NA 50‐52 . Many studies support the efficacy of combination of low‐dose IM HBIG with ETV (or TDF) given indefinitely as an effective prophylaxis against HBV recurrence after LT irrespectively of anti‐HBs levels 53‐56 . Vatansever et al recently reported that low‐dose IM HBIG combined with a NA (LAM, ADV, ETV, TDF or telbivudine) results in 4.5% and 5.8% of HBV recurrence in the first and third year after LT respectively 53 .…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 99%